Des céréales et du lait au Sahara et au Sahel, de l’épipaléolithique à l’âge des métaux - Christian Dupuy (Afriques)
The diversity of the current culinary traditions in the Sahara and the Sahel, centered on cereals and giving to dairies a very variable part, indicates the complexity of their history. This article proposes a synthesis and reflections on this subject from the known archaeological remains.It remains difficult to recognize the use of wild cereals as food resources from 20 000 BC (time of appearance of the stone grinding equipment in the Libyan desert). New investigations, some of which successful recently, may be able to give determining elements to elucidate this question. The first attempts of pearl millet domestication appear during the IIIrd millennium B.C. in the West African Sahel region. Domestication of other cereals which are still cultivated today seems to begin at least two thousand years later, judging by the discoveries of botanical rests. The development of cereal culture implies the management of sowing, grain storing, guarding and protection of fields and defense of the harvests. It further implies economic specialisation, development of craftsmanship, envy, development of trading, and hence, the accentuation of different social categories and political rivalries.Since the beginning of breeding in Africa, that is to say from the VIth millennium B.C. to present, Saharan herdsmen have exploited the dairy production of their animals. Several documented sources demonstrate this: figurative milk-producing female animals and milking scenes in Saharan rock art, slaughtering of young calves and kids in the Libyan desert, fat from cow’s milk preserved inside potsherds found in the Tadrart Akoukas.